2008
DOI: 10.14742/ajet.1203
|View full text |Cite
|
Sign up to set email alerts
|

Using activity theory and its principle of contradictions to guide research in educational technology

Abstract: This paper describes how activity theory (AT) and its principle of contradictions may be relied on to guide research in educational technology. The paper begins with a theoretical overview of AT and of its principle of contradictions. It follows with a synthesis of studies that have used AT as a lens to study information and communication technologies (ICTs) in educational contexts. We analyse educational technology studies that have focused on contradictions in terms of their underlying assumptions, research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 33 publications
0
64
0
4
Order By: Relevance
“…Murphy and Rodriguez-Manzanares (2008) provide a thorough review of these studies, focusing on how they have focused on the principle of contradictions, a key aspect of activity theory. These contradictions occur when there is a 'misfit within elements, between elements, between different activities, or between different developmental phases of a single activity' (Kuutti, 1996, p. 34).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Murphy and Rodriguez-Manzanares (2008) provide a thorough review of these studies, focusing on how they have focused on the principle of contradictions, a key aspect of activity theory. These contradictions occur when there is a 'misfit within elements, between elements, between different activities, or between different developmental phases of a single activity' (Kuutti, 1996, p. 34).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Participants frequently indicated that they experienced the learning process and the tools being used as different to their traditional experiences, hence the strong articulation of how the Extended Cyberhunt context contradicts the traditional text-book, chalk board and 'teacher chalk-and-talk' context. The rules and the division of labour (Murphy & Rodriguez-Manzanares, 2008;Hardman, 2005aHardman, , 2005b were experienced as different, as participants indicated that they were not confined to one place, but could move around, ask questions and were assisted by peer-facilitators from other groups, not just from the facilitator. This became evident in the interest and collaborative results section, as the data suggest the formation of a sense of community (see Activity Theory triangle, Figure 1) as a result of the sharing of ideas, asking for assistance, by listening to problems that were experienced, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The interacting components within the mediational triangle (See Figure 1) of an activity system are the subject, object, tools, community, rules and division of labour (Murphy & Rodriguez-Manzanares, 2008). Hardman (2005aHardman ( , 2005b states that within such a system learning is not viewed as transmission, but as transformation, hence learning within an activity system could be seen as an evolving process mediated by tools and social interaction.…”
Section: Activity Theory and The Extended Cyberhunt Interventionmentioning
confidence: 99%
“…The analysis of contradictions and tensions is particularly useful in studies involving educational technology given the (usually purposeful) disturbances these projects have in organisations, such as schools. The analysis of the tensions that emerge in educational technology projects from the perspective of teachers can help understand how changes in educational practice might take place in school contexts (Murphy and Rodriguez-Manzanares 2008).…”
Section: Methodsmentioning
confidence: 99%